The treasure of the Turkish pasha. - Biber, Yehoash 1937-; Shulevitz, Uri 1935-. (New York Scribner, 1968)
A former Palestinian guardsman leads a party, which includes his teen-age son, across the Sinai desert to find a map which will lead them to a treasure stolen many years before by a Turkish pasha.
Translation of Otsar ha-peòhah ha-Turki.
Keywords: Deserts -- Fiction; Adventure and adventurers -- Fiction